The Environmental Impact of Palm Oil: Introduction for Students of Tasmania University, Australia - Chalil, Diana; Barus, Riantri; Nababan, Ester Sorta Mauli; Sembiring, Pramio Garson; Hasanuddin; Sofyan, Rudy; Tulus (Journal of Saintech Transfer, 2021)
Palm oil is one of the most demanded commodities globally, which has led to a significant increase in its production and raised issues regarding its environmental impact. However, many of these issues are not based on substantial evidence. To provide a proportional picture on the oil palm industry, Universitas Sumatera Utara (USU), the University of Tasmania (UTAS) and the Association of Indonesian Palm Oil Entrepreneurs (GAPKI) have collaborated to carry out this program. The program was conducted for seven days through classroom lectures and field trip activities, involving 14 students and two supervisors from UTAS and four USU students. Pre and post-tests were conducted to evaluate the impact of the program. The results showed changes in participants’ knowledge and perception regarding the environmental, social, and economic effects of the oil palm industry. Therefore, this program could be considered an effective counter to misleading Indonesian palm oil industry issues.